Faktor Penyebab dan Peranan Orang Tua terhadap Remaja Penyalahguna Narkoba di Yayasan Lantera Minangkabau - Putri, Melyulida; Hasan, Marwisni; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
Problems studied by the researchers discovered a phenomenon in the field in the lives of many people found these bad boys with attitudes and behaviors of ignorance, no one involved in drug abusers, engage in promiscuity, gambling, and theft. Based on the above phenomenon researchers raised concerns about the study: factors causing teenagers abusing drugs and the role of parents of adolescent drug abusers. The purpose of research to determine the causes of adolescent drug abuse and the role of parents of adolescent drug abusers.This type of research is a descriptive study and the population is involved adolescent                 drug abusers in Minangkabau Lantera foundation. Sampling in this study uses total sampling ie sampling done to the whole population. Sources of data in this study is primary data and secondary data. Primary data were obtained from a questionnaire completed by the adolescent drug abusers while the secondary data obtained from the foundation. Data collection tool used was a questionnaire and data analysis techniques using percentage analysis. Based on the results of this research is the general statement that the causes of adolescent drug abusers in Lantera Foundation Minangkabau are pretty much on the category and the role of parents of adolescent drug abusers in Minangkabau Lantera Foundation in the category pretty much.